Assessing reasoning in the classroom - Stiggins, Rick; Assessment Training Institute (Portland, Oregon : Assessment Training Institute, 1999)
This video shows what it means to be a proficient reasoner and problem solver and then offers practical suggestions for transforming that vision of achievement into classroom assessments that can help student succeed
Title from cover
Presenter: Rick Stiggins
Keywords: Educational tests and measurements; Educational evaluation